Cellhesion VP enhances the immunomodulating potential of human mesenchymal stem cell-derived extracellular vesicles. (April 2021) - Kim, Eun Seo; Kida, Katsuhiko; Mok, Jongsoo; Seong, Yeonwoo; Jo, Seo Yeon; Kanaki, Tatsuro; Horikawa, Masato; Kim, Kyung-Hee; Kim, Tae Min; Park, Tae Sub; Park, Joonghoon
Abstract: Mesenchymal stem cell (MSC) transplantation is a promising therapy for regenerative medicine. However, MSCs grown under two-dimensional (2D) culture conditions differ significantly in cell shape from those in the body, with downregulated stemness genes and secretion of paracrine factors. Here, we evaluated the effect of 3D culture using Cellhesion VP, a water-insoluble material composed of chitin-based polysaccharide fibers, on the characteristics of human Wharton's jelly-derived MSCs (hMSCs). Cellhesion VP significantly increased cell proliferation after retrieval. Transcriptome analyses suggested that genes involved in cell stemness, migration ability, and extracellular vesicle (EV) production were enhanced by 3D culture. Subsequent biochemical analyses showed that the expression levels of stemness genes including OCT4, NANOG, and SSEA4 were upregulated and migration capacity was elevated in 3D-cultured hMSCs. In addition, EV production was significantly elevated in 3D cells, which contained a distinct protein profile from 2D cells. Gene and drug connectivity analyses revealed that the 2D and 3D EVs had similar functions as immunomodulators; however, 3D EVs had completely distinct therapeutic profiles for various infectious and metabolic diseases based on activation of disease-associated signaling pathways. Therefore, EVs from Cellhesion VP-primed hMSCs offer a new treatment for immune and metabolic diseases.